Riboflavin Inhibits Histamine-Dependent Itch by Modulating Transient Receptor Potential Vanilloid 1 (TRPV1) - Lee, Kihwan; Choi, Young In; Im, Sang-Taek; Hwang, Sung-Min; Lee, Han-Kyu; Im, Jay-Zoon; Kim, Yong Ho; Jung, Sung Jun; Park, Chul-Kyu (Frontiers in Molecular Neuroscience, 2021)
Riboflavin, also known as vitamin B2, is found in foods and is used as a dietary supplement. Its deficiency (also called ariboflavinosis) results in some skin lesions and inflammation, such as stomatitis, cheilosis, oily scaly skin rashes, and itchy, watery eyes. Various therapeutic effects of riboflavin, such as anticancer, antioxidant, anti-inflammatory, and anti-nociceptive effects, are well known. Although some studies have identified the clinical effect of riboflavin on skin problems, including itch and inflammation, its underlying mechanism of action remains unknown. In this study, we investigated the molecular mechanism of the effects of riboflavin on histamine-dependent itch based on behavioral tests and electrophysiological experiments. Riboflavin significantly reduced histamine-induced scratching behaviors in mice and histamine-induced discharges in single-nerve fiber recordings, while it did not alter motor function in the rotarod test. In cultured dorsal root ganglion neurons, riboflavin showed a dose-dependent inhibitory effect on the histamine- and capsaicin-induced inward current. Further tests were conducted to determine whether two endogenous metabolites of riboflavin, flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), have similar effects to those of riboflavin. Here, FMN, but not FAD, significantly inhibited capsaicin-induced currents and itching responses caused by histamine. In addition, in TRPV1-transfected HEK293 cells, both riboflavin and FMN blocked capsaicin-induced currents, whereas FAD did not. These results revealed that riboflavin inhibits histamine-dependent itch by modulating TRPV1 activity. This study will be helpful in understanding how riboflavin exerts antipruritic effects and suggests that it might be a useful drug for the treatment of histamine-dependent itch.